2013
DOI: 10.1051/epjconf/20134107005
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast spectroscopy of UV-induced DNA-lesions — on the search for strategies which keep DNA alive

Abstract: Abstract. UV-induced photolesions are studied in the visible and IR. While structural distortions of the DNA-backbone at the moment of light absorption are prerequisite for CPD-formation, strain from the backbone guides Dewar-formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Formation of photolesions is too fast for the triplet to be a precursor but the doorway state may be involved. [106][107] Figure 10: Schematic Jablonski diagram of the processes following UV excitation in thymine and uracil. 105…”
Section: Tautomersmentioning
confidence: 99%
“…Formation of photolesions is too fast for the triplet to be a precursor but the doorway state may be involved. [106][107] Figure 10: Schematic Jablonski diagram of the processes following UV excitation in thymine and uracil. 105…”
Section: Tautomersmentioning
confidence: 99%
“…). Short time and steady‐state spectroscopic studies have shown that depending on the local conformation of the DNA bases relative to each other in the duplex, reactions to different photoinduced products occur . It is interesting that the vast majority of UV‐induced lesions are created at pyrimidine–pyrimidine sites, indicating that the photoexcitation is somewhat concentrated at such positions.…”
Section: Structure Of Uv‐induced Dna Lesionsmentioning
confidence: 99%